miR-140 inhibits osteosarcoma progression by impairing USP22-mediated LSD1 stabilization and promoting p21 expression - Wei Liu; Dunwei Wang; Lidi Liu; Lin Wang; Ming Yan (Elsevier, 2021)
Osteosarcoma is a bone tumor frequently diagnosed in children and young adults. Despite advances in chemotherapy and surgical resection, tumors metastasize in 30% of osteosarcoma patients. In addition, side effects caused by chemotherapeutic drugs, as well as the development of chemoresistance, highlight the need to identify the molecular mechanisms involved in the pathogenesis of osteosarcoma. We compared 65 osteosarcoma samples to their adjacent normal tissues, as well as commercially obtained osteosarcoma cell lines with normal osteoblast cell lines, and identified a role for the microRNA (miR)-140/ubiquitin-specific protease 22 (USP22)/lysine-specific demethylase 1 (LSD1)/p21 axis in the development of osteosarcoma. Osteosarcoma tissues and cells exhibited poor miR-140 and p21 expression, whereas the expression of USP22 and LSD1 was increased. Overexpression of miR-140 inhibited cell proliferation, migration, and invasion and promoted cell apoptosis by directly targeting USP22, resulting in its decreased expression. Overexpression of USP22 reversed the effects of miR-140 overexpression in osteosarcoma cells. Overexpression of miR-140 or USP22 knockdown led to the ubiquitination and degradation of LSD1. miR-140 overexpression also suppressed tumorigenesis in vivo. This study revealed a role for miR-140 in the restriction of osteosarcoma development and identified miR-140 as a potential target for therapeutic intervention.